(untitled) (American International Journal of Nursing Education and Practice, 2021)
This study investigates the present COVID-19-related medical waste generation scenario and suggests a way forward from the perspective of lower-middle-income countries like Bangladesh. Bangladesh is a densely populated vulnerable country in the perspective of the COVID-19 induced biomedical waste management field. The pandemic COVID-19 has already created enormous instability in healthcare waste handling and subsequent recycling around the world. The medical waste management sector in Bangladesh is struggling and COVID-19 makes the situation even more complicated. A rigorous time-series calculation was done to determine the facemask and medical waste load during COVID-19 in Bangladesh from March 8, 2020, to September 13, 2021 period. Results showed that about 1,58,10,400 pieces of facemask are disposed of alone in different urban areas which is equivalent to 517 tons of solid waste while extra 5,203 tons of biomedical waste is added every day to regular waste streams during this pandemic. The findings of this study suggest that these extra tons of hazardous waste threaten the aquaculture of the country and promote the risk of contagious diseases to the waste workers especially women and as well as at the community level. The findings also reveal that this pandemic has already created a hindrance to achieving the country’s SDGs by 2020. JEL Classification Codes: L65, Q53.